“Corporality is the horizon of expectations…”: Arkadii Dragomoshchenko as a Reader of Maurice Merleau-Ponty - Korchagin, Kirill M. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2020)
This paper considers the influence of the French school of phenomenology represented by Maurice Merleau-Ponty on Akradii Dragomoshchenko’s poetics. Dragomoshchenko (1946—2012) was a St Petersburg writer, an important figure of the Russian literature of the last quarter of the twentieth and early twenty-first centuries. Dragomoshchenko’s interest in the latest European and American thought played an important role in his creative activity both as a source of quotations and allusions in his prose and poetic works written between the 1980s and 2000s and an impulse for a structural transformation of his own creative manner. Phenomenology of Perception by Maurice Merleau-Ponty was a philosophical text which played an important precedent role in the process. Its translation into English became available to the poet starting with the 1980s. A specific variant of the phenomenology of the body worked out by the French philosopher forms a conceptual apparatus in the 1990s, using which Dragomoshchenko reflects his own creative method with the help of fiction. Most comprehensively, the process is represented in Dragomoshchenko’s last major work, Chinese Sun (1997), a novel which can be considered a vivid example of interference of philosophical and poetic language. The understanding of sensory perception and its role in human subjectivity substantiated by Merleau-Ponty in Phenomenology of Perception is used to analyse how visual and kinesthetic experience influences the writer. The novel employs different stylistic means which make it possible to emphasise the phenomenological nature of the author’s approach. Also, the writer uses numerous lyrical insertions, retardations and retrospections, functionally marked use of certain grammatical forms (primarily, verbs of imperfective aspect and present tense), etc. The author of the article analyses such means to demonstrate the role played by the phenomenological perspective in Dragomoshchenko’s creative work and the evolution of his poetics between the 1980s and 2000s.